Mango Pests and Beneficial Insects - Daniel Carrillo; Rita Duncan; Jorge Peña (EDIS)
This document provides an overview of the major pests affecting mango crops in Florida, including thrips, mirids, mealybugs, scales, mites, whiteflies, blackflies, beetles, and red-banded thrips. It details their life cycles, damage symptoms, and control measures, emphasizing the importance of monitoring and selecting appropriate pesticides. The document also highlights the role of natural enemies and the need for adherence to pesticide regulations to ensure effective pest management and compliance with safety guidelines. Date first printed: October 1993.